The Effect Of Adding Red Dragon Fruit Skin On The Quality Of Dadiah Gelato - Yunianti, Badriyah Maulidya; Faridah, Anni; Holinesti, Rahmi; Andriani, Cici (Universitas Negeri Padang, 2024)
Indonesia is geographically located on the equator, which is a country with a tropical climate. Ice cream is a snack that is suitable to eat when the weather is hot. One type of ice cream is gelato. Gelato is a type of frozen dairy food dessert which is a processed product made from cow's milk and is included in the low-fat ice cream category. The main ingredients for gelato include cow's milk, whipped cream, egg yolks and sugar. Gelato has lower fat content (4-8%) and total solids (32-42%) than regular ice cream, but usually has higher sugar content (16-21%) to provide a smooth, scoopable texture. Ways are needed to develop gelato, such as adding curd and natural coloring from fruit. Dadiah has weaknesses in terms of its sour taste and fishy aroma which people don't like, therefore there needs to be innovation or efforts that can be made to attract people's interest in consuming dadiah, such as by adding dragon fruit skin. 30-35% of dragon fruit is the skin of the fruit, but it is often just thrown away as trash and considered waste without being used for anything more useful. Dragon fruit skin contains quite high levels of antioxidant compounds which are able to fight oxidation in the body. Red dragon fruit skin contains vitamin B1, vitamin B2, vitamin B3 and vitamin C, protein, fat, carbohydrates, crude fiber, thiamine, niacin, pyridoxine, cobalamin, glucose, phenol, betacyanin, polyphenols, carotene, phosphorus, iron and flavonoids. This research aims to analyze the effect of adding 15%, 25% and 35% of red dragon fruit skin on the quality of the color, aroma, texture, taste and preferences of the dadiah gelato produced. This type of research is a pure experiment using a Completely Randomized Design method. The data used is primary data obtained directly from 3 expert panelists by filling in the organoleptic test format for the quality of gelato with the effect of adding red dragon fruit skin. The data obtained is then tabulated in table form and Analysis of Variance (ANOVA) is carried out, if Fh>Ft then followed by the Duncan Test. The results of the research showed that there was a significant effect of adding red dragon fruit skin of 15%, 25% and 35% on color quality (pink fanta). The best result from the gelato quality test with the addition of red dragon fruit skin was 35%.